2011
DOI: 10.1103/physrevb.84.115306
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism behind the switching of current induced by a gate field in a semiconducting nanowire junction

Abstract: We propose a new orbital controlled model to explain the gate field induced switching of current in a semiconducting PbS-nanowire junction. A single particle scattering formalism in conjunction with a posteriori density functional approach involving hybrid functional is used to study the electronic current; both first and higher order Stark effects are explicitly treated in our model. Our calculation reveals that after a threshold gate-voltage, orbital mixing produces p-components at the S atoms in the partici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

8
1

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 25 publications
4
24
0
Order By: Relevance
“…This hybrid functional has been shown to give a much better description of transmission than the pure functional. 51 In addition, a recent density of states analysis in transition metal compounds 52 has shown that the B3LYP results agree well with the results obtained from embedded dynamical mean-eld theory. The convergence thresholds for total energy, root mean square and maximum density are set at 10 À9 , 10 À8 , and 10 À6 a. u. respectively.…”
Section: Computational Detailssupporting
confidence: 60%
“…This hybrid functional has been shown to give a much better description of transmission than the pure functional. 51 In addition, a recent density of states analysis in transition metal compounds 52 has shown that the B3LYP results agree well with the results obtained from embedded dynamical mean-eld theory. The convergence thresholds for total energy, root mean square and maximum density are set at 10 À9 , 10 À8 , and 10 À6 a. u. respectively.…”
Section: Computational Detailssupporting
confidence: 60%
“…The stable conformations of the aforementioned probes and their corresponding Zn­(II)/probe complexes were determined through optimization of their geometries (Figure ). A posteriori hybrid density functional method (B3LYP) that includes a portion of the exact Hartree–Fock exchange, and a 6-311+G­(d,p) Gaussian basis set , were used for our calculation. We used an implicit solvent model (taking water as the solvent) to mimic the solvent effect.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] Recently, the possibility of a single PbS nanowire (NW) based FET device has also been explored both in experiments and theoretical studies. 13,14 In a very recent experimental study, band-gap controlled PbS nanocrystals of various sizes were synthesized to study the effect of bandgap energy on the photovoltaic performance. 15 This study has shown that an optimal band-gap of 1.2 eV maximizes the photovoltaic device performance.…”
Section: Introductionmentioning
confidence: 99%